2012
DOI: 10.1111/j.1600-051x.2012.01930.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant marginal bone level: a systematic review and meta‐analysis of studies comparing platform switching versus conventionally restored implants

Abstract: PS technique appeared to be useful in limiting bone resorption. Nevertheless, these data should be interpreted cautiously as significant heterogeneity and possible publication bias were noted. Further research is needed to identify the factors most associated with successful outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
161
0
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(178 citation statements)
references
References 46 publications
5
161
0
12
Order By: Relevance
“…Actually, all parallel arm designs (as the present report) appear to demote the effect size of PS on marginal bone levels when compared to split‐mouth designs as extrapolated from Annibali et al. (2012) and Chrcanovic et al. (2015) but are less prone to incur in type I errors (incorrect rejection of the null hypothesis) due to the increased number of patients recruited (independent statistical units).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Actually, all parallel arm designs (as the present report) appear to demote the effect size of PS on marginal bone levels when compared to split‐mouth designs as extrapolated from Annibali et al. (2012) and Chrcanovic et al. (2015) but are less prone to incur in type I errors (incorrect rejection of the null hypothesis) due to the increased number of patients recruited (independent statistical units).…”
Section: Discussionmentioning
confidence: 96%
“…2014, Annibali et al. 2012, Laurell & Lundgren 2011). In this sense, block randomization was done only after implant installation to avoid foreknowledge of the treatment assignment and possible tendencies to favour either group by the modification of the surgical protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So that long term, well-conducted RCT to validate eff ect of PS is conceded even in most recently publishing review. [6][7][8] Th is systematic review was reported following the recommendations for preferred reporting items for systematic reviews and meta-analyses. 9 Th e author state clearly all details for systematic review and meta-analysis studies including implant data (number, system, hex, level, loading, and follow-up period), patients demographic data and type of radiograph used for bone loss assessment.…”
Section: Commentarymentioning
confidence: 99%